2021
DOI: 10.3389/fphar.2020.614413
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Aquilaria sinensis (Lour.) Gilg and Aucklandia costus Falc. Volatile Oils Exerts Antidepressant Effects in a CUMS-Induced Rat Model by Regulating the HPA Axis and Levels of Neurotransmitters

Abstract: The Aquilaria sinensis (Lour.) Gilg (CX)–Aucklandia costus Falc. (MX) herbal pair is frequently used in traditional Chinese medicine prescriptions for treating depression. The volatile oil from CX and MX has been shown to have good pharmacological activities on the central nervous system, but its curative effect and mechanism in the treatment of depression are unclear. Therefore, the antidepressant effect of the volatile oil from CX–MX (CMVO) was studied in chronic unpredictable mild stress (CUMS) rats. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…The antidepressant effect of Aquilaria sinensis and S. costus EO, a traditional herbal pair in TCM to treat depression has been strengthened only recently. Inhalative administration revealed antidepressant activity in chronic unpredictable mild stress rats by regulating the HPA axis and levels of monoamine and cholinergic neurotransmitters, immunity and gastrointestinal function [ 299 ]. It is stated that the comprehensive effects on the central nervous system may, among others, be related to DEH from S. costus EO, and agarospirol in A. sinensis EO.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antidepressant effect of Aquilaria sinensis and S. costus EO, a traditional herbal pair in TCM to treat depression has been strengthened only recently. Inhalative administration revealed antidepressant activity in chronic unpredictable mild stress rats by regulating the HPA axis and levels of monoamine and cholinergic neurotransmitters, immunity and gastrointestinal function [ 299 ]. It is stated that the comprehensive effects on the central nervous system may, among others, be related to DEH from S. costus EO, and agarospirol in A. sinensis EO.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…It is stated that the comprehensive effects on the central nervous system may, among others, be related to DEH from S. costus EO, and agarospirol in A. sinensis EO. The two compounds are known as analgesics and potent antagonists of dopamine D 2 and serotonine 5-HT 2A receptor binding [ 299 , 300 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…The FST is described in previous reports (Li et al, 2020), and the reduction in immobility duration is identified with an antidepressant-like effect. Mice were forced to swim in a glass cylinder (diameter 20 cm, water depth 25 cm) filled with water 25 ± 1 °C.…”
Section: Forced Swim Testmentioning
confidence: 94%
“…In contrast, traditional Chinese medicine with definite curative effects and few adverse reactions has received widespread attention. Because of its multicomponent, multi-target, and multi-pathway effects, traditional Chinese medicine has highlighted its unique advantages in the prevention and treatment of PTSD ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments for depression mainly focus on the monoaminergic system, and the commonly used antidepressants are selective serotonin reuptake inhibitors, or norepinephrine reuptake inhibitors. Unfortunately, studies have shown that one-third of patients do not respond to the initial treatment, and almost half of them have a secondary response, often producing adverse reactions such as sexual dysfunction, nausea, tremor, and insomnia ( Li et al, 2020a ; Zhuo et al, 2020 ). To combat depression, the identification of natural medicines with better curative effects and increased safety is urgently needed.…”
Section: Introductionmentioning
confidence: 99%